2009
DOI: 10.1089/tmj.2008.0046
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of a Telerehabilitation Program to Support Chronically Ill and Disabled Elders in Their Homes

Abstract: Chronic illnesses account for approximately 75% of all healthcare costs in the United States today, resulting in functional limitations and loss of independence, as well as increased medical expenditures. The elderly population is at a higher risk for developing chronic conditions, increasing their risk for disabilities. Given the rapid growth of the aging population, and the chronic illnesses, disabilities, and loss of functional independence endemic to elders, novel methods of rehabilitation and care managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 48 publications
(40 reference statements)
1
76
1
Order By: Relevance
“…Perhaps this is due to the fact that several telerehabilitation initiatives retrieved in this study have emerged as technological developments more than real clinic applications. In contrast to reports from other regions around the world [9], [10], [12], our findings demonstrate that in Latin America there are no previous studies of economic and assistive benefits regarding these kind of assistive technologies used by ei-ther government or private health care systems to provide rehabilitation services. Therefore, a huge multidisciplinary effort by clinicians and researchers is necessary to validate-from the clinical and economic point of view-the profitability of assistive technologies used in remote urban areas in each country in this region.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Perhaps this is due to the fact that several telerehabilitation initiatives retrieved in this study have emerged as technological developments more than real clinic applications. In contrast to reports from other regions around the world [9], [10], [12], our findings demonstrate that in Latin America there are no previous studies of economic and assistive benefits regarding these kind of assistive technologies used by ei-ther government or private health care systems to provide rehabilitation services. Therefore, a huge multidisciplinary effort by clinicians and researchers is necessary to validate-from the clinical and economic point of view-the profitability of assistive technologies used in remote urban areas in each country in this region.…”
Section: Discussioncontrasting
confidence: 99%
“…A retrospective study with 155 patients and 155 control subjects shown that the costs of hospital bed days of care (1,449 days) in the year before the implementation of telerehabilitation programs totaled approximately $1,500,000, which decreased more than around $804,000 the year following the implementation of the telerehabilitation program, which represents a 46% decrease in costs and a decrease of 826 days of care [10]. Likewise, primary care and geriatric visits decreased by over 100 during that year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike those covered by the VA, these individuals cannot get coverage for mobility devices needed for IADL because these activities are not limited to mobility functions "in the home" [1][2]. We know that the use of ATDs is associated with decreased disability [3][4], which reduces falls and subsequent hospital admissions/institutional care [4][5][6][7][8][9][10][11] and, thus, healthcare costs. It makes sense then, in the context of healthcare reform (reduction in emergent care and rehospitalization [48][49], implementation of the medical home model [50]) that the savings be reinvested in expanding the provision of ATDs.…”
Section: Limitationsmentioning
confidence: 99%
“…This CMS determination conflicts with legislative actions that mandate individuals with disabilities be provided with the necessary supports to live as independently as possible in their communities [1]. Even though increased use of assistive technology devices (ATDs) has been cited as one of the reasons for decreasing disability [3][4] and has positively affected health-related costs by reducing falls and, subsequently, hospital admissions and institutional care [4][5][6][7][8][9][10][11], fewer than 50 percent of older adults with chronic disability and fewer than 25 percent of individuals with recent disabilities received ATDs [12]. Further, only 6 percent of community-dwelling Medicare beneficiaries received any ATDs from Medicare [13].…”
Section: Introductionmentioning
confidence: 99%